Studies on the effect of H+ carrier toward ionic conduction properties in alginate-ammonium sulfate complexes–based polymer electrolytes system - Nurhasniza, Mamajan Khan; Noor M, Norman; Ahmad, S Samsudin (SAGE Publications Ltd, 2022)
The present work highlights the contribution of ammonium sulfate (NH4)2SO4 as H+ carriers in alginate-based solid polymer electrolytes (SPEs) that were successfully prepared via a solution casting technique. The Fourier transform infrared analysis revealed that molecular interactions between the host polymer and the ionic dopant complexes occurred at the wavenumbers 3700–2500 cm-1, 1800–1500 cm-1, and 1200–900 cm-1. These regions corresponded to the O-H stretching, COO− and C-O-C, moieties of alginate, respectively, which coordinated with the H+ carrier from (NH4)2SO4. At ambient temperature, the optimum ionic conductivity was obtained at 3.01 × 10−5 S cm-1 for the sample containing 10 wt.% of (NH4)2SO4. The IR-deconvolution approach shows that the ionic conduction enhancement is governed by the ionic mobility and the diffusion coefficient of H+ carriers, and the findings show that the present biopolymer, which is an alginate-based SPEs system, has an excellent possibility to be used as electrolytes for application in electrochemical devices